2022
DOI: 10.3390/educsci13010037
|View full text |Cite
|
Sign up to set email alerts
|

Schooling and Occupational Outcomes in Adults with ADHD: Predictors of Success and Support Strategies for Effective Learning

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is a neurobehavioral disorder that is usually diagnosed in childhood. It is characterized by attention deficits, hyperactivity, and impulsivity leading to significant impairment in academic, occupational, familiar, and social functioning. Most of the literature has been focusing on the impact of this condition on infancy and preadolescence, but little is known on its consequences in adulthood. This narrative review addresses this gap by focusing on the studies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 119 publications
0
14
0
Order By: Relevance
“…Dialogic Science and MADIT provide the researcher with, respectively, a theoretical basis and a methodological approach for describing and measuring the use of natural language. This approach is based on the encoding of 24 Discursive Repertories (DRs) 3 , each one representing a specific modality of using natural language (see Supplementary Materials 3). Humans can create countless narrative realities through language, nevertheless all these realities of sense can be described as a set of these modalities which, in turn, create a discursive configuration 4 that can either change over time or remain static.…”
Section: Theoretical and Methodological Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dialogic Science and MADIT provide the researcher with, respectively, a theoretical basis and a methodological approach for describing and measuring the use of natural language. This approach is based on the encoding of 24 Discursive Repertories (DRs) 3 , each one representing a specific modality of using natural language (see Supplementary Materials 3). Humans can create countless narrative realities through language, nevertheless all these realities of sense can be described as a set of these modalities which, in turn, create a discursive configuration 4 that can either change over time or remain static.…”
Section: Theoretical and Methodological Referencesmentioning
confidence: 99%
“…The diagnosis (following the criteria of DSM-5) requires the presence of developmentally inappropriate levels of hyperactive-impulsive and/or inattentive symptoms for at least 6 months in different settings, causing impairments in living [2]. ADHD is mostly diagnosed in children and adolescents, but meta-analysis showed that adults present this symptomatology too, although with lower prevalence [3][4][5].…”
mentioning
confidence: 99%
“…These interventions sought to improve symptomatic aspects of academic life and success, such as attention, executive functioning, and anxiety, as well as aiding in other skills such as organisational techniques. The acquisition process of university students with ADHD is greatly enhanced with assistance, particularly in terms of executive functioning and anxiety control (Varrasi et al, 2022). Amongst these is coaching, which helps in self-determination and the setting of specific goals, aspects that are very helpful for students with this disorder (* Prevatt et al, 2017).…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…In spite of this difficulties, the academic challenge at university level appears to pose significant barriers for individuals with ADHD, specifically with regard to executive functions, metacognition, and emotional regulation, all of which impact learning processes (Varrasi et al, 2022). High levels of ADHD symptomatology and low levels of executive functioning cause these students to suffer a negative relationship with their impairment, which in turn, leads to low selfesteem (Dorr and Armstrong, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion [35], people who develop ADHD present a wide range of cognitive deficits, but they are only manifested in some EFs (fundamentally, cold EFs; see model by Zelazo and Carlson [28]). Several prospective studies have shown in individuals with ADHD the association of executive function deficits with poorer academic performance [38], the occurrence of substance use disorders [39], and other psychiatric comorbidities [40].…”
Section: Of 14mentioning
confidence: 99%